Efficacy and safety of liraglutide in Indian adolescents with obesity - I. S. Kochar; A. Sethi (Wiley, 2019)
Summary Aim The aim of this study was to evaluate the efficacy and safety of liraglutide in adolescents with obesity. Materials and methods Patients (n = 41) received injection liraglutide for at least 12 weeks and their pre‐baseline and post‐baseline characteristics were recorded and analysed. The key parameters analysed were weight, height, body mass index (BMI), fasting insulin and sugar, 1 h insulin and glucose, 2 h insulin and glucose, HbA1c, cholesterol, triglycerides, serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, thyroid stimulating hormone and bone. Results There was a significant decrease (p < 0.001) in body weight, BMI, fasting, 1 h post‐glucose tolerance and 2 h glucose tolerance. The changes from baseline to the end of study were for body weight − 6.5 ± 4.2 kg and BMI -2.35 ± 1.30 kg m−2. Systolic blood pressure decreased from 119.25 ± 12.50 to 114.53 ± 9.53 mmHg and diastolic blood pressure from 70.69 ± 14.52 to 70.82 ± 8.85 mmHg. Liver enzymes had improved from 34.36 ± 12.23 (serum glutamic oxaloacetic transaminase), 38.08 ± 21.02 (serum glutamic pyruvic transaminase) to 33.52 ± 11.23 (p = 0.03) and 33.99 ± 13.16 (p = 0.01), respectively. Cholesterol and triglyceride had improved from 152.46 ± 24.74 and 124.41 ± 33.27 to 151.71 ± 23.46 (p = 0.14) and 120.76 ± 26.22 (p = 0.009), respectively. Conclusion In conclusion, treatment with liraglutide in adolescents with obesity offers an efficacious and safe alternative to patients who are not responding to other available modalities.